Modeling of the blood oxygen and heart rate measurement system - Lyashenyk, A.V.; Nykyrui, R.I.; Goyanyuk, I.V. (Physics and Chemistry of Solid State, 2024)
Monitoring heart rate and blood oxygen content is an integral part of monitoring health and physiological parameters of a person’s condition. Thus, measurement of oxygen content and heart rate becomes a rather popular problem. To solve the task set in this work, it is necessary to conduct a detailed analysis of the area and determine the main physical properties of blood at different indicators of the oxygen content in it. Also, when conducting this study, attention should be paid to the influence of the oxygen content in the blood on the heart rhythm of a person.